How do you prove: cosx- (cosx/(1-tanx))= (sinxcosx)/(sinx-cosx)?

1 Answer

(sinx cosx) / (sinx - cosx) = cosx - [(cosx) / ( 1 - tan x)]

(sinx cosx) / (sinx - cosx) = cosx - {(cos x ) / [ 1 - ( sinx / cosx)]}

(sinx cosx) / (sinx - cosx) = cosx - {(cosx) / [(cosx - sinx) / cosx]}

(sinx cosx) / (sinx - cosx) = cosx - {(cosx) [cosx / (cosx - sinx)]}

(sinx cosx) / (sinx - cosx) = cosx - [ (cos ^2 x) / (cosx - sinx)]

(sinx cosx) / (sinx - cosx) = [cosx( cosx - sinx ) - (cos ^2 x) ] / (cosx - sinx)

(sinx cosx) / (sinx - cosx) = (cos ^2 x - cosx sinx - cos ^2 x ) / (cosx - sin x)

(sinx cosx) / (sinx - cosx) = - (cosx sinx) / ( cosx - sinx )

(sinx cosx) / (sinx - cosx) = - (cosx sinx) / [ - ( sinx - cosx)]

(sinx cosx) / (sinx - cosx) = (-cosx sinx) / [ - ( sinx - cosx)]

(sinx cosx) / (sinx - cosx) = (cosx sinx) / ( sinx - cosx)

Source here